L’éducation au patrimoine à l’école primaire : une éducation citoyenne ? - Sylviane Blanc-Maximin (Recherches en Éducation)
This article is interested in the possible links between heritage education and citizenship education in the french primary school when pupils from 9 to 12 years old make heritage with objects or immaterial elements in their villages. The study of the educational device, the follow-up of its real progress during debates in class and during a collective exposure as well as results of a questionnaire to 90 pupils show that this type of heritage education participle of the acquisition ok skills of “to live together”.